(3aJGhi aj LhGR GdJbdjO hGdefY ef GdaJhi HePgH GdfGUQ aj GdWdGbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hHYO aEfG fYde GdcGaI eef hba Ydi cJGHf gPG ef CUd GdePgH GdTQja hCghGf GdOjf GdMfja s
(3BNQgG (B:s
(3GdNUdg GdQGHYI eLGfHI GdCNdGb GdPejeI hbO PcQ gPg GdUaGJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdabg GdESdGejs